Polyphenols and health: Interactions between fibre, plant polyphenols and the gut microbiota. Issue 4 (10th November 2017) - Edwards, C. A.; Havlik, J.; Cong, W.; Mullen, W.; Preston, T.; Morrison, D. J.; Combet, E.
Abstract: A high‐fibre diet and one rich in fruit and vegetables have long been associated with lower risk of chronic disease. There are several possible mechanisms underpinning these associations, but one likely important factor is the production of bioactive molecules from plant‐based foods by the bacteria in the colon. This links to our growing understanding of the role of the gut microbiome in promoting health. Polyphenolic‐rich plant foods have been associated with potential health effects in many studies, but the bioavailability of polyphenol compounds, as eaten, is often very low. Most of the ingested molecules enter the large intestine where they are catabolised to smaller phenolic acids that may be the key bioactive effectors. Dietary fibres, present in plant foods, are also fermented by the bacteria to short‐chain fatty acids, compounds associated with several beneficial effects on cell turnover, metabolism and eating behaviour. Polyphenols and fibre are often eaten together, but there is a lack of research investigating the interaction between these two groups of key substrates for the colonic bacteria. In a project funded by the Biotechnology and Biological Sciences Research Council Diet and Health Research Industry Club, we are investigating whether combining different fibres and polyphenol sources can enhance the production of bioactive phenolic acids to promote health. This could lead to improved dietary recommendations and to new products with enhanced potential health‐promoting actions.